Effect of sinapic acid ester derivatives on the oxidative stability of omega-3 fatty acids rich oil-in-water emulsions. (30th March 2020) - da Silveira, Tayse Ferreira Ferreira; Cajaíba, Letícia Maeda; Valentin, Leonardo; Baréa, Bruno; Villeneuve, Pierre; Castro, Inar Alves
Highlights: Lipophilization of sinapic acid, electrical charge of the emulsifier and pH were evaluated. pH and the electrical charge modulated the antioxidant effectiveness of sinapic acid esters. DTAB emulsifier and neutral pH provided the best oxidative stability. Increase of length chain reduced the secondary products of oxidation using SDS as emulsifier. Abstract: Oil-in-water (O/W) emulsions are important delivery systems of omega-3 fatty acids (n-3 FA). We investigated the effect of sinapic acid esters concentration and chain length, the electrical charge of the emulsifier and emulsion pH on the oxidative stability of n-3 FA rich O/W emulsions. Echium oil was applied as n-3 FA source. A 2 4 factorial design was used to simultaneously evaluate these factors. Peroxide value, malondialdehyde, 2, 4-heptadienal and 2, 4-decadienal were measured in the emulsions. pH and the electrical charge of the emulsifier modulated the antioxidant effectiveness of sinapic acid esters, while concentration was not relevant. The combination of positively charged emulsifier with neutral pH provided the best oxidative stability for echium oil emulsions. Our results also suggested that the increase of length chain of sinapic acid, from C4 to C12, reduced the secondary products of oxidation, when echium oil emulsions were prepared using negatively charged emulsifier under acidic conditions.